QORQIT ATA JIRLARI HÁM QARAQALPAQLAR TARIYXI - Jawlıbaeva, N. (SCIENCE and SOCIETY, 2022)
The article analyzes the relationship between the book "Korgyt ata" and the history of the Karakalpak people, and the impact of this book on the Karakalpak epics.
Keywords: Epic of Edige; historical; V.V.Bartold; genre features; typological similarities